PARTISIPASI TIM PENCEGAHAN PEMBERANTASAN PENYALAHGUNAAN PEREDARAN GELAP NARKOBA (P4GN) KABUPATEN SUKOHARJO DALAM UPAYA PEMENUHAN HAK PENDIDIKAN ANAK JALANAN - Nursihan, Ratna; Permata Hartanto, Rima Vien; ., Wijianto (PKn Progresif, 2016)
Street children are particularly vulnerable to the dangers of drugs. The number of street children in Sukoharjo move the hearts of volunteers of P4GN team Sukoharjo in the implementation soft rehabilitation of street children through school for street children. Sukoharjo P4GN team formed for cases of drug abuse had gone into all districts in Indonesia. This research aims to determine the participation of P4GN team Sukoharjo in fulfilling the education?s rights of street children, street children school implementation process, constraints encountered, and the impacts after implementation of that program. This research uses descriptive qualitative research. Selection of informants is determined by purposive sampling technique. Sources of data obtained from informants and a review of documents, and also from techniques of data collection is done through interview, observation, and documentation study. To test the validity of the data, using data triangulation technique. The technique of data analysis using interactive analysis, which is done in three stages, namely data reduction, data presentation, and conclusion.